The Effect of Auditor Switching, Audit Delay, Audit Tenure, and Firm Size on Audit Quality (Empirical Study of Manufacturing Companies in the Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange in 2017-2021) - Ningrum, Lusiana; Ningrum, N.ARumiasih.; Asvariwangi, Verni (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2023)
Study This aim For know influence variable Auditor Switching, Audit Delay, Audit Tenure, Firm Size to Company Audit Quality manufacture sector industry goods consumption listed on the IDX on 2017-2021 years . Method taking sample using purposive sampling and obtained sample as many as 18 companies during five year so that the data is analyzed as many as 90 observations with use logistic regression with tool analysis using SPSS version 25. Results study show that Firm Size matters positive to top audit quality examiner report finance on company with positive direction _ And company big tend get more audit quality ok . Meanwhile, Auditor Switching, Audit Delay and Audit Tenure do not influential significant to old audit quality engagement that occurred between KAP and company client And change of auditors by company client And ever audit report issued No influence audit quality however influence accuracy time And relevance from report finance the .